The telomere-associated (TLO) genes of Candida dubliniensis - Haran, John (Trinity College (Dublin, Ireland). School of Dental Science, 2014)
Candida species are members of the Saccharomycetuceae and are the most common cause of fungal infections in humans. Diseases caused by these yeasts range from superficial infections (e.g. oropharyngeal & vulvovaginal candidiasis) to life-threatening systemic infections (e.g. candidemia). C. albicans is the most prevalent species associated with such infections. C. dubliniensis is a closely related species, yet is significantly less virulent. Evidence for this disparity has been supported with in vivo and in vitro virulence models. Genome comparisons were carried out to identify differences in gene content in an attempt to explain the contrasting virulence between these closely related species. The TeLOmere-associated (TLO) gene family had the largest difference in copy number between the species, with 14 (plus one pseudogene) in C. albicans compared to 2 in C. dubliniensis. The TL(h were originally identified as putative transcriptional activators with some homology to the Med2 subunit of the Mediator complex in Saccharomyces cere visiae A range of in silico analyses, as well as molecular techniques such as Southern immunoblotting and polymerase chain reaction (PCR) were performed to characterise the TLO gene family. Quantitative real-time PCR (qRT-PCR) was used to measure expression of the genes and it was observed that expression of both genes increases w ith growth stage, with TLOl expression higher than TL02. Homology to Med2 in S. cerevisiae was confirmed in silico, which supports previous assertions by other groups. Interestingly, allelic heterozygosity was observed for TL02. with one intact and one truncated copy in Wu284.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin